Rhythmic Wave Patterns on Ambient Pressure Tympanometry in Patients With Objective Tinnitus-associated Pathologies. Issue 3 (March 2020) - Sayyid, Zahra N.; Thai, Anthony; Swanson, Austin; Hosseini, Davood K.; Fitzgerald, Matthew B.; Ma, Yifei; Vaisbuch, Yona
Abstract : Objective: To introduce the concept of ambient pressure tympanometry (APT) and its association with pathologies that may present with objective tinnitus. Study Design: Retrospective case series. Setting: Tertiary referral center. Subjects and Methods: Audiologists performed APT on adult patients as part of routine audiological testing. Ears with myoclonus and patulous Eustachian tube (PET) were identified via review of patient history and physical examination. All other conditions were verified via computed tomography (CT) temporal bone imaging. Ears with conditions that could impair tympanic membrane compliance, such as otosclerosis or tympanic membrane perforation, were excluded. APT findings were analyzed via a novel algorithm. Results: A radiographic finding associated with objective tinnitus was confirmed in 67 ears that underwent CT imaging; 45 (67%) of these ears displayed rhythmic APT wave patterns. These included 28 ears with superior semicircular canal dehiscence, 4 ears with sigmoid sinus dehiscence, 6 ears with internal carotid artery dehiscence, 4 ears with glomus tumor, and 3 ears with encephalocele. In addition, we identified three ears with myoclonus and one ear with PET. In a subset of 30 ears with objective tinnitus symptoms that underwent CT imaging, 22 displayed rhythmic waves; of these 22 ears, 20 (91%) had a radiographic finding associated with objective tinnitus. Conclusions: Rhythmic APT wave patterns are common and may be associated with numerous temporal bone pathologies that may present with objective tinnitus. APT is a simple, rapid, and widely available tool that warrants further study to determine its value in screening of these otologic conditions.